1998
DOI: 10.1177/107319119800500205
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure of the State-Trait Anger Expression Inventory for Middle-Aged Men and Women

Abstract: Recently, Forgays, Forgays, and Spielberger (in press) reported the first exploratory factor analysis of the total 44-item State-Trait Anger Expression Inventory (STAXI) by gender. The analyses were based on a sample of over 700 male and female university students and identified quite well six of the original STAXI scales and subscales. In addition, a seventh factor, "Feel-Like-Expressing-Anger," emerged for women. In the present study, we examined the STAXI responses from a middle-aged adult population. Explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 22 publications
0
42
1
1
Order By: Relevance
“…We found no difference in scores by gender, similar to the Russian results 17 . However, our data was different from previous studies in American adults on Trait/Anger 16 and the first Brazilian sample on Anger/In 13 that showed slightly higher values for men compared to women. In our findings some items of the State/Anger (5, 7, and 8) and Anger/ Control (21, 24, 31, 35, and 38) presented lower correlation with the total construct, but they did not affect the overall construct.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…We found no difference in scores by gender, similar to the Russian results 17 . However, our data was different from previous studies in American adults on Trait/Anger 16 and the first Brazilian sample on Anger/In 13 that showed slightly higher values for men compared to women. In our findings some items of the State/Anger (5, 7, and 8) and Anger/ Control (21, 24, 31, 35, and 38) presented lower correlation with the total construct, but they did not affect the overall construct.…”
Section: Resultscontrasting
confidence: 99%
“…Although its psychometric properties had already been assessed for Brazilian college students and Navy recruits 13 , the present factor analysis have showed construct validity close to the Spielberger's original theoretical ground of anger psychopathology. Previous American 15,16 and Russian 17 studies found that STAXI is a consistent instrument. Similarly to the Spielberger's State-Trait Anger Expression Inventory application Azevedo et al…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Anger has also been discussed as either a "state" or a "trait" (e.i. Spielberger and Sydeman, 1994;Forgays, Spielberger, Ottaway, and Forgays, 1998) suggesting that "personality factors" as well as temporary states are factors in anger (Klein, 2011).…”
Section: Anger In the Workplacementioning
confidence: 99%